Composition of the colon microbiota in the individuals with inflammatory bowel disease and colon cancer - Acar, Ceren; Celik, Sibel Kucukyildirim; Ozdemirel, H Ozgur; Tuncdemir, Beril Erdem; Alan, Saadet; Mergen, Hatice (Folia microbiologica, 2024)
The human intestine is a habitat for microorganisms and, recently, the composition of the intestinal microbiota has been correlated with the etiology of diseases such as inflammations, sores, and tumors. Although many studies have been conducted to understand the composition of that microbiota, expanding these studies to more samples and different backgrounds will improve our knowledge. In this work, we showed the colon microbiota composition and diversity of healthy subjects, patients with inflammatory bowel disease (IBD), and colon cancer by metagenomic sequencing. Our results indicated that the relative abundance of prokaryotic and eukaryotic microbes differs between the healthy vs. tumor biopsies, tumor vs. IBD biopsies, and fresh vs. paraffin-embedded tumor biopsies. Fusobacterium, Escherichia-Shigella, and Streptococcus genera were relatively abundant in fresh tumor biopsies, while Pseudomonas was significantly elevated in IBD biopsies. Additionally, another opportunist pathogen Malasseziales was revealed as the most abundant fungal clade in IBD biopsies, especially in ulcerative colitis. We also found that, while the Basidiomycota:Ascomycota ratio was slightly lower in tumor biopsies compared to biopsies from healthy subjects, there was a significant increase in IBD biopsies. Our work will contribute to the known diversity of prokaryotic and eukaryotic microbes in the colon biopsies in patients with IBD and colon cancer.
Keywords: Metabarcoding; Humans; nádory tračníku; mikrobiota; Colonic Neoplasms; střevní sliznice; Inflammatory Bowel Diseases; Crohn Disease; Microbiota; Ulcerative colitis; lidé; 18SrRNA; idiopatické střevní záněty; Crohnova nemoc; Mycobiome; 16SrRNA; Basidiomycota; Intestinal Mucosa; Crohn’s disease